Answer:
x = 2 , y = 7
Explanation:
Since
y-3x = 1
y = 3x+1 - equation 1
2y-x = 12 - equation 2
Since we are using substitution method,
we will substitute equation 1 into equation 2.
![2(3x + 1) - x = 12 \\ 6x + 2 - x = 12 \\ 5x + 2 = 12 \\ 5x = 12 - 2 \\ 5x = 10 \\ x = (10)/(5) \\ = 2](https://img.qammunity.org/2023/formulas/mathematics/college/cksz6f5v87o9jr5j1l9t0a0o5b2p4s3fe1.png)
Now we substitute x into equation 1 to find y.
![y = 3(2) + 1 \\ = 6 + 1 \\ = 7](https://img.qammunity.org/2023/formulas/mathematics/college/xl7d2jioyta5ajhd2k3h19kltw3ys5e5z3.png)
Therefore x = 2, y = 7.